Amnistía Internacional y Educación en Derechos Humanos - Iñaki Gómez (Universidad de La Rioja, 2013)
Amnesty International is a worldwide movement of volunteer activists, who make efforts to prevent some of the worst human rights violations committed by some governments, working mainly to obtain freedom for all the prisoners of conscience, getting impartial trials for political prisoners, fighting for the death penalty abolition and the eradication of torture. A.I. looks for stopping the extrajudicial executions and "disappearance". In order to get these proposals, A.I. makes efforts to promote every human rights consecrated in the Universal Declaration of Human Rights and another international rules, using educative programs, not only in the school, seeking for the education of the society, looking for joining education with action, always allowing the active participation in the defence of human rights to its helpers. This article explains these principles on the importance of the education in the fight for the human rights, developing its main objectives, usual work and some suggestions about useful didactic material from the point of view of A.I, that is to say, the confidence in the preventive worth of education.